Review papersAethiopathogenesis of mastocytosis: current options - Lange, Magdalena; Niedoszytko, Marek; Niedoszytko, Bogusław; Gleń, Jolanta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Mastocytosis is a group of rare, heterogeneous disorders characterized by abnormal growth and/or accumulation of mast cells (MC) in one or more organ systems. Signs and symptoms of the disease mostly result from MC-derived mediators and MC organ infiltration. Here we present major advances that have been made over the last 10 years in the understanding of mastocytosis pathogenesis. Genetic findings indicate the key role of activating mutation of c-kit, encoding the stem cell receptor (SCF) in systemic mastocytosis. However, this mutation does not explain all aspects and the heterogeneity of the disease. Numerous factors, such as other gene defects, genetic polymorphisms, abnormal expression of cell surface adhesion antigens, dysregulation of MC proliferation and apoptosis have also been discussed as contributing to the highly complex pathogenesis of mastocytosis, which still remains unclear.